Punching shear analysis of post-tensioned slabs - Melges, Jose Luiz P. [UNESP]; Pinheiro, Libanio M; Takeya, Toshiaki (My University, 2005)
Experimental results and conclusions about punching shear slab failures are presented. The main analysed aspects are the strength influence of the shear reinforcement (studs) and the post-tensioning with unbonded tendons for an intemal slab-column connection. All the models have the same dimensions (square of 2500mm, depth of l 60mm) and are centrally loaded through a square metallic plate with side equal to 180mm. The mean value of the compressive strength of concrete is 50MPa, measured by standard cylinders. A comparison between the experimental results and those given by standards is presented. The following ones are considered: fib (1999), FIP (1999), ACI318 (1999), and the Brazilian Code NBR6118 (2003). This comparison intends to verify if the codes accurately predict the connection punching shear strength.